2012
DOI: 10.1136/bcr-2012-007425
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis nodosa presenting as haematuria following strenuous exercise

Abstract: SummaryPolyarteritis nodosa (PAN) can affect many organ systems but usually presents with a systemic illness characterised by malaise, weight loss, myalgia, arthralgia and signs of end-organ damage. Here, we report a case of PAN that presented acutely in a previously well 46-year-old man with visible haematuria and loin pain coinciding with an episode of strenuous exercise. Initially, the patient was thought to have suffered renal trauma, but subsequent investigations revealed intrarenal aneurysms typical of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Many clinicians often neglect to consider testicular pain as a presenting symptom of vasculitis. To our best knowledge, our patient is the youngest of all the patients who had testicular pain as an initial manifestation of systemic PAN ( Table 1, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). In addition to testicular pain, our patient displayed diffuse myalgias, unexplained weight loss meeting the diagnosing criteria for PAN [19].…”
Section: Discussionmentioning
confidence: 84%
“…Many clinicians often neglect to consider testicular pain as a presenting symptom of vasculitis. To our best knowledge, our patient is the youngest of all the patients who had testicular pain as an initial manifestation of systemic PAN ( Table 1, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). In addition to testicular pain, our patient displayed diffuse myalgias, unexplained weight loss meeting the diagnosing criteria for PAN [19].…”
Section: Discussionmentioning
confidence: 84%
“…Bing et al reported a case of PAN presenting clinically in a 46 year old fit male with loin pain and frank haematuria following an episode of strenuous exercise [9] . Initial concerns of renal trauma were subsided by investigations revealing an intra-renal aneurysm, confirming PAN as a diagnosis and its resolution following a course of immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%